Risiko likuiditas bank syariah: Seberapa penting? - Faraz, Laode (Maliki Interdisciplinary Journal, 2024)
Liquidity risk is one of the crucial aspects in the operation of Islamic banks that affects the stability and overall performance of sharia-based financial institutions. In Indonesia, Bank Muamalat has been a successful example in facing challenges and risks, especially during the economic crisis of 1998. Factors such as sharia principles in the operational system, financial support from the Islamic Development Bank (IDB), and maintained bank performance have helped Bank Muamalat remain stable. Financial performance analysis, including profitability ratios, equity ratios, and liquidity ratios, is key in measuring the health of Islamic banks. With effective liquidity risk management, Islamic banks can maintain their resilience and stability amidst financial market dynamics. This literature study highlights the importance of liquidity risk for Islamic banks and emphasizes the need for appropriate risk management strategies to maintain the continuity of Islamic bank operations in the future